Study on Serological Markers and Brain Structural Changes in Early Clinical Stage of Alzheimer’s Disease in Cold Regions. - Yin, Changhao; Chen, Lingyu; Wang, Jianhang; Zhao, Weina (Actas Espanolas de Psiquiatria, 2025)
Background: Subjective cognitive decline (SCD) and mild cognitive impairment (MCI) represent early clinical manifestations of Alzheimer’s disease (AD). Recent research has highlighted serum markers and changes in brain structure as promising tools for diagnosing cerebral disorders. This study investigated serum biomarkers and brain structural changes in the early clinical stage of AD affected individuals residing in a cold region. Methods: Clinical data from patients with SCD or MCI and from normal controls, who were tested at Hongqi Hospital Affiliated to Mudanjiang Medical College from January 2018 to December 2023, were retrospectively analysed. According to clinical classification, the patients were categorised into SCD (n = 60), MCI (n = 60) and normal control groups (n = 70). The magnetic resonance imaging data, serum levels of amyloid β 1-40/42, exosomal miRNA (34a/34c/135a) and apolipoprotein E (ApoE) genotype were collected and analysed. Results: The mean diffusivity values in the bilateral parahippocampal gyrus, inferior longitudinal bundle, right inferior fronto-occipital tract and posterior cingulate gyrus in the SCD group decreased relative to those of the MCI group (all p < 0.05). Conversely, the fractional anisotropy values in the bilateral parahippocampal gyrus, inferior fronto-occipital tract, inferior longitudinal tract and posterior cingulate gyrus in the SCD group increased (all p < 0.05). Compared with the normal control group, the MCI and SCD groups showed elevated levels of serum Aβ1-40 and Aβ1-42 and exosomal miRNA-34a and miRNA-34c (all p < 0.05) and decreased exosomal miRNA-135a expression (p < 0.05). The serum levels of Aβ1-40, Aβ1-42 and exosomal miRNA-34a and miRNA-34c in the SCD group were lower than those in the MCI group (all p < 0.05), whereas miRNA-135a level was higher (p < 0.05). The proportions of ApoE ε3/3 in the normal control group was the highest (62.86%), and the proportions of ApoE ε2/4, ε3/4 and ε4/4 in the MCI group were the highest (38.33%, 26.67% and 10.00%, respectively). Conclusion: Changes in brain structure and serum biomarkers (miRNAs and Aβ) are evident in the early stages of AD, and the proportion of ApoE alleles vary in early AD. These findings may contribute to the development of an early recognition model for AD.